An Overview Learning Management Systems (International Journal of Innovative Research in Engineering & Management, 2021)
Systems for teaching. Have been found to  promote active learning and a positive attitude to  information acquisition. Another of the secrets to the  Eidolons' effective and efficient use is how participants  embrace and perceive them. The present study is motivated  by the need of understanding instructors' and students'  perspectives on Imps in order to anticipate future problems  and create a constructive instructional atmosphere and a  devoted userbase. The following issues are discussed at a  Russian institution where the system is being incorporated:  shareholder qualification and willingness to utilize LMS, as  well as their judgments of the state's accessibility, potency,  and usefulness. The research reveals significant disparities  in students' and instructors' perceptions of several parts of  LMS, that should be considered when enhancing the game's  effectiveness and raising devotion to it. Learning. They are  studied and discussed in this article.
Keywords: Higher Education; E-Learning; Online Learning; Learning Management Systems